Negotiating Literacy Culture in South Papua: Literary Activities among Third-Semester English Language - Desca Angelianawati; Rawuh Yuda Yuwana; Marni Bawawa (English Language Teaching Prima Journal (ELT), 2026)
The study investigates the literary activities of third-semester students in the English Education Study Programme at Universitas Musamus Merauke and examines the structural and institutional factors that constrain their engagement with literature. While existing studies on literacy in Indonesian higher education have tended to focus on urban and better-resourced institutional contexts, research addressing the specific conditions of literacy culture in peripheral eastern Indonesian universities, particularly in South Papua, remains scarce. This study addresses that gap by situating the problem within the particular social, geographic, and institutional realities of Universitas Musamus Merauke. Situated in Merauke, South Papua, a region where access to literary resources remains limited and literacy rates among the general population stand at approximately 72%, the study draws on classroom observation, interviews with secondary school teachers, and a systematic library study to collect its data. A fishbone diagram organised around the 5M framework and the USG (Urgency, Seriousness, Growth) method are employed to identify and rank the causal factors behind students' low literary engagement. The findings indicate that a low overall literacy level constitutes the most pressing concern, compounded by the scarcity of organised literary activities on campus, insufficient book procurement, and limited student awareness of available reading resources. The study proposes a set of contextually grounded responses and discusses their potential contribution to character formation and the development of critically engaged graduates in a culturally diverse educational context.